Tax Morale after the Reunification of Germany: Results from a Quasi-Natural Experiment - Lars P. Feld; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2007)
This paper provides a comparison of tax morale between inhabitants of East and West Germany in its post-reunification period, using three World Values Survey/European Values Survey waves between 1990 and 1999. The setting of German reunification is particularly interesting for the analysis of tax morale as it is close to a natural experiment. Many factors can be controlled because they are similar, as, e.g., a common language, similar education systems and a shared cultural and political history prior to the separation after the Second World War. As a consequence, an East-West comparison has a methodological advantage compared to cross-country studies. Our findings show higher tax morale in East than in West Germany. However, in only 9 years after reunification, tax morale values strongly converged, especially due to a strong change in the level of tax morale in the East.
Keywords: H26; H73; D78; C93; 330; Tax Morale; Tax Evasion; Deterrence; Quasi-Natural Experiment